ANALYSIS OF THERMAL PROTECTIVE PERFORMANCE OF ALUMINUM FOIL INSULATION SUITS DUE TO VARIATIONS IN AIR GAP THICKNESS - Mahendra, Kiemas Aji Andika; Wahyudi, Slamet; Siswanto, Eko; Yao, Jiafeng (International Journal of Mechanical Engineering Technologies and Applications, 2025)
This study investigates improving the thermal protective performance (TPP) of aluminum foil insulation suit by incorporating air gaps to reduce heat transfer. Firefighters rely on personal protective equipment that must meet NFPA 1971 standards, requiring a minimum TPP of 35 cal/cm². Using a heat transfer bench scale test, three-layer aluminum foil insulation suits with air gaps ranging from 0 mm to 7.68 mm were tested. Each sample was exposed to heat until the innermost layer reached 55°C. The analysis of temperature, heat transfer rate, heat flux, second-degree burn time, and thermal resistance revealed that a TPP exceeding 35 cal/cm² was achieved at a 6.4 mm air gap, peaking at 36.30 cal/cm² at 7.68 mm. The increase in TPP with larger air gaps was due to higher thermal resistance and extended burn times. Thus, a minimum air gap of 6.4 mm is recommended for firefighter clothing to meet safety standards.